Impacto de la reforestación en la población del eje de carretera Iquitos Nauta orientada al desarrollo sostenible, Iquitos, Loreto 2021 - Upiachihua Hidalgo, Aldo Jahir (2022)
This study was carried out on Iquitos Nauta road, in the project “Recovery of degraded ecosystems in the are of the influence of Iquitos-Nauta road, districts of San Juan Bautista and Nauta province of Maynas, Loreto department”, with the purpose of knowing the impact of reforestation on the population of Iquitos-Nauta road oriented to sustainable development. From the obtained results, it is found that 76% of the beneficiaries come from Iquitos (54%), 20% from Nauta, 8% from San Martin Region and 24% from other provinces of Loreto region, as well as 65% of those who live in the villages near their plantations and 35% live on their own plantation or farm. The species that are used for reforestation, among the forest species: mahogany, marupa, cedar, screw, rosewood, chestnut, and in fruit species: macambo, copoazú, umarí, uvilla. 56% are interested in GOREL continuing to support reforestation activities and 41% are not interested; 79% show interest in reforestation being developed in other populated centers along the highway, 58% consider that environmental education is important. 64% consider that reforestation along the highway axis will improve the economy of the population in the near future, 16% consider that reforestation increases the presence of wildlife in the area. Reforestation is beneficial for the rural populations of our Amazon, lacking more work in basic areas such as basic education, environmental education, legislation, use of natural resources.